Clasificación geomecánica del macizo rocoso que permite plantear las alternativas de refuerzo y sostenimiento en el nivel 1 de la veta Negra de la mina Alonzo, del área minera El Condado ubicada en la parroquia San Juan de Cerro Azul, Cantón Atahualpa, Provincia de El Oro - Arteaga Valencia, Silvia Alexandra (2025)
This research work was carried out in the parish of San Juan de Cerro Azul, Canton Atahualpa, Province of El Oro, in the mining area El Condado code 30000934, whose objective is focused on the geomechanical classification of the rock mass in order to propose alternatives for reinforcement and support at level 1 of the Veta Negra gallery of the Alonzo mine, The development of this research was carried out based on a qualitative and quantitative analysis that allowed the collection of information and interpretation, including the field phase starting from the collection of samples in the Veta Negra Level 1 gallery, the laboratory phase that allowed the analysis of the samples collected and the office phase where the interpretation and writing of the data obtained was carried out. The El Condado concession code 30000934 is located within the Saraguro Formation, the Alonzo mine has an interior mine lithology characterized by diorite and andesite, being the andesite the lithology present in the Veta Negra gallery of Level 1 which has a length of 412.08 m and along this there is evidence of the presence of fractures in the walls of the massif and a fault zone. The index properties of the rock massif in Level 1 of the Veta Negra gallery show variability in the six samples collected, being the moisture content in variable ranges from 0.26% to 0.61%, the specific gravity from 2.75 g/cm3 to 2.78 g/cm3, a specific gravity of 2.75 g/cm3 to 2.78 g/cm3, a specific gravity of 2.75 g/cm3 and a specific gravity of 2.78 g/cm3. 78 g/cm3, an absorption coefficient of 0.31 to 0.66, its porosity ranges from 0.02% and 7.35% and the compactness of the rock high, with a rock strength of 66.01 MPa and 123.50 MPa, whose average indicates a rock of medium strength. The geomechanical classification through the application of the RMR14, Barton's Q and GSI systems, allows a correlation and a better characterization and classification of the massif, taking into account characteristics of the massif such as; rock strength, number of discontinuities, filling present in the openings, as well as the size of the openings, weathering of the walls, length and distance between fractures and the presence of water. Allowing to correlate the values of the different methods applied and classify the massif in three zones; the first as a good zone of Class II with Good Quality, the second classified as a regular zone of Class III with Medium Quality and the third as a bad zone of Class V with Bad Quality, being this the fault zone. With the objective of defining the optimum support, the characteristics obtained were taken into account, such as the dimensions of the gallery with a width of 1.80 m, height of 2.10 m and arch of 0.30 m, the index properties, the characteristics and geomechanical classification, determining three zones, these defined as good, regular and bad. Defining that 5 the best option is the application of bolts and mesh with a layer of shotcrete and the use of trusses respectively.